PHYSICAL AND ORGANOLEPTIC CHARACTERISTICS OF TAMARIND PASTE (Tamarindus Indica L) WITH MODIFIED ELEPHANT CASSAVA (Manihot Esculenta) DERIVATIVE PRODUCT THICKENER - Rahayu, Putri Nanda; Prabowo, Sulistyo; Rachmawati, Maulida (Jurnal Pangan dan Agroindustri, 2024)
This research was conducted to determine the effect of physical properties on elephant cassava derivative products as a thickener for tamarind paste. This study used a non-factorial completely randomized design (CRD) with 2 treatments, namely types of thickener (modified starch and mocaf) at 5 different concentrations (0%, 1%, 3%, 5%, and 10%) with 3 repetitions. The addition of 10% elephant cassava mocaf flour had the highest value based on the viscosity test with a value of 5624 mPas, in the 10% solubility test the addition of modified starch has a value of 90.47%, the speed with heating at 80℃ ranges from 45-66 seconds and the organoleptic test for taste attributes is 2.04- 2.48.